DIGITAL MATURITY AS A FACTOR OF STRATEGIC MANAGEMENT EFFECTIVENESS IN ORGANIZATIONS - S.Q. Saydalieva (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines digital maturity as a determinant of strategic management effectiveness,  focusing  on  project-oriented  organizations  navigating  digital transformation.  Drawing  on  comparative  analysis,  qualitative  organizational assessment, and synthesis of contemporary literature, the study maps six core maturity dimensions-data  and  analytics,  process  automation,  technology  integration, organizational  culture,  strategic  leadership,  and  customer  engagement-against  a spectrum  of  management  outcomes.  Organizations  at  low  maturity  levels  exhibit  a characteristic cluster of dysfunctions: fragmented digitalization, manual coordination dependency,  weak  analytical  infrastructure,  communication  overload,  and  limited scalability-conditions that directly erode strategic coherence. A phased development framework  is  proposed,  comprising  process  formalization,  centralized  project management, CRM integration, KPI-based monitoring, business intelligence adoption, and digital capability building. The findings contribute to digital strategy literature and offer actionable guidance for practitioners in emerging market contexts.